Clays and Clay Minerals, Vol. 55, No. 2, 177–188, 2007. - Kiipli, Tarmo; Kiipli, Enli; Kallaste, Toivo; Hints, Rutt; Somelar, Peeter; Kirsima¨e, Kalle (The Clay Minerals Society, 2007)
The composition of altered volcanic ash of the Late Ordovician Kinnekulle bed was studied in geological sections of the Baltic Paleobasin. The composition of altered ash varies with paleosea depth from northern Estonia to Lithuania. The ash bed in shallow shelf limestones contains an association of illite-smectite (I-S) and K-feldspar, with the K2O content ranging from 7.5 to 15.3%. The limestone in the transition zone between shallow- and deep-shelf environments contains I-S-dominated ash with K2O content from 6.0 to 7.5%. In the deep-shelf marlstone and shale, the volcanic ash bed consists of I-S and kaolinite with a K2O content ranging from 4.1 to 6.0%. This shows that authigenic silicates from volcanic ash were formed during the early sedimentary-diagenetic processes. The composition of the altered volcanic ash can be used as a paleoenvironmental indicator showing the pH of the seawater or porewater in sediments as well as the sedimentation rate.
Altered Volcanic Ash As An Indicator Of Marine Environment, Reflecting Ph And Sedimentation Rate - Example From The Ordovician Kinnekulle Bed Of Baltoscandia
Clays and Clay Minerals, Vol. 55, No. 2, 177–188, 2007. Altered Volcanic Ash As An Indicator Of Marine Environment, Reflecting Ph And Sedimentation Rate - Example From The Ordovician Kinnekulle Bed Of Baltoscandia. Tarmo Kiipli; Enli Kiipli; Toivo Kallaste; Rutt Hints; Peeter Somelar; Kalle Kirsima¨e. DOI: 10.1346/CCMN.2007.0550207. Copyright © 2007, The Clay Minerals Society.
Keywords: Periodicals; Geology; Baltoscandia; K-bentonite; Kinnekulle; Marine Environment; Ordovician; pH; Sedimentation Rate; Volcanic Ash